HUBUNGAN KONSUMSI TABLET FE DENGAN KEJADIAN ANEMIA PADA KEHAMILAN DI PUSKESMAS SIPAYUNG TAHUN 2016 - Elsie anggreni (Menara Ilmu, 2018)
Efforts to avoid the occurrence of anemia in pregnant women The Ministry of Health of theRepublic of Indonesia has made a program of giving fe in pregnant women. Health data inRiau Province in 2010, found anemia nutrition in pregnant women by 48%. This study aims todetermine the relationship of fe tablet consumption with the incidence of anemia in pregnancyat Sipayung Rengat Public Health Center. The research method used is Analytical method withCross Schealal design. The result of the research was obtained from 46 respondents about theconsumption of fe tablet showed 24 respondents (52,17%) consumed fe tablet and 22respondent (47,83%) did not consume fe tablet. The incidence of anemia in the respondentsthat 22 respondents (47.83%) had anemia and 24 respondents (52.17%) had normal Hb levels(not anemia). The result of bivariate research with Chi-square test result (x2) obtained p value= 0.001 means that p value is smaller than a value (0.05) so ho rejected it is concluded thatthere is a significant relationship between consumption of Fe tablet with anemia incidence withOdds Ratio OR) = 0.125. The conclusion of this study, There is a significant relationshipbetween the relationship of consumption of Fe tablet with the incidence of anemia at SipayungRengat Public Health Center in 2016.Keywords: Fe tablet consumption, Anemia, Pregnancy